Adaptation of Climate-Responsive Building Design Strategies and Resilience to Climate Change in the Hot/Arid Region of Khartoum City, Sudan - Osman, Mubarak Mohammed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
ABSTRACT: Climate change has become one of the most discussed topics of last few decades. It has inspired researchers of the built environment to develop climate-responsive design strategies. These strategies are essential for the construction sector to take advantage of abundant renewable resources in the local climate. Implementation of such strategies has the potential to reduce reliance on fossil fuels, which are considered a major cause of ozone depletion and resultant global warming. The permanent alterations to Earth’s ecological system change have made Khartoum City in Sudan vulnerable to climate change. Significant impacts of climate change to nature, structures, and human well-being have already been noticed. Though the Sudanese government and parastatals have made efforts to address these climate induced problems, improvements remain insufficient. Indices show the climate alterations occurring in Khartoum include irregular heat waves, increased relative humidity, drought, and extreme flooding. In addition, climate-related phenomena like intense thunderstorms and sand-dust storms have become more frequent than ever. Even though the brunt of these climatic events is primarily felt outdoors, they all result in uncomfortable and challenging to manage indoor conditions. In this research, Khartoum’s climate data from 1981 to 2015 was analyzed and compared to identify trends in temperature, humidity, wind speed, and rainfall. This trend analysis indicates acute climate change. The Meteonorm Company created the hourly energy plus (EPW) file for Khartoum from the averages of basic climate parameters recorded and available for Khartoum from 1996 to 2015. Meteonorm 7.2.1 evaluated the city’s future projected hourly energy plus (EPW) file up to 2070. To counter 2070’s projected climatic conditions, resilient design strategies were evaluated to minimize energy usage and optimize thermal comfort for building users today and in the future. Contemporary design strategies of 2015 and projected design strategies for 2070 were compared and the findings revealed that design strategies must shift towards more active cooling and away from passive cooling to reduce energy usage and achieve optimal user thermal comfort in 2070. Moreover, natural ventilation and active heating will no longer be beneficial design strategies. Two-stage evaporative cooling is anticipated to become the most sustainable and effective climate-responsive design strategy for all seasons in Khartoum. Passive design strategies with increased resilience should be adapted for use with Khartoum’s underutilized renewable resources to reduce future active-cooling demand and to optimize thermal comfort. Keywords: Climate Change, Khartoum Region Climate Data, Thermal Comfort, Design Strategies
Doctor of Philosophy in Architecture. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2019. Supervisor: Asst. Prof. Dr. Harun Sevinç
Keywords: Architecture Department; Residential Buildings - Design and Construction - Climate-responsive design - Khartoum City (Sudan); Architecture, Domestic; Climate Change, Khartoum Region Climate Data, Thermal Comfort, Design Strategies